2012
DOI: 10.1371/journal.pone.0029547
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Urinary Mercury between Children with Autism Spectrum Disorders and Control Children

Abstract: BackgroundUrinary mercury concentrations are used in research exploring mercury exposure. Some theorists have proposed that autism is caused by mercury toxicity. We set out to test whether mercury concentrations in the urine of children with autism were significantly increased or decreased compared to controls or siblings.MethodsBlinded cohort analyses were carried out on the urine of 56 children with autism spectrum disorders (ASD) compared to their siblings (n = 42) and a control sample of children without A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Overall, the finding of increased levels of several toxic metals in urine of children with ASD agrees with two previous studies [15, 77], but disagrees with one large study [78] and one small study [79]. This disagreement is similar to that of the 40 case-control studies discussed in the introduction, in which about half observed levels of increased toxic metals.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Overall, the finding of increased levels of several toxic metals in urine of children with ASD agrees with two previous studies [15, 77], but disagrees with one large study [78] and one small study [79]. This disagreement is similar to that of the 40 case-control studies discussed in the introduction, in which about half observed levels of increased toxic metals.…”
Section: Discussionsupporting
confidence: 69%
“…A study by Wright et al [78] in the United Kingdom investigated urinary levels of several toxic metals in 56 children with ASD compared to 121 neurotypical children, and did not find significant differences in levels of mercury, antimony, cadmium, or lead. The results for mercury and cadmium are consistent with the present study, but the results for antimony and lead are not.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown no link between mercury body burdens and autism (Ip, Wong et al 2004; Hertz-Picciotto, Green et al 2010; Albizzati, More et al 2012; Wright, Pearce et al 2012). However, a reanalysis of data generated by Ip et al showed there was in fact an association between mercury levels and autism that had been overlooked due to a statistical error (Desoto and Hitlan 2007).…”
Section: Environmental Factors In Autism and Immune Dysfunctionmentioning
confidence: 99%
“…Several recent studies have also failed to find a relationship between a higher body burden of toxic metals and an ASD diagnosis [14,15,16,17]. Although studies have shown an association between an ASD diagnosis and various toxic metals, such as cadmium (Cd), lead (Pb), and arsenic (As), the bulk of the research has focused on mercury (Hg).…”
Section: Introductionmentioning
confidence: 99%